A rare cytological diagnosis of primary Non-Hodgkin’s lymphoma of parotid gland - Biswajit Dey; Vasudha Goyal; Nidhi Mahajan; Shyama Jain; Seema Kaushal; Anoop Raj (Mediterranean Journal of Hematology and Infectious Diseases)
Primary malignant lymphoma of parotid gland is relatively rare and constitutes about 4 to 5 % of extra-nodal lymphomas. Majority of them are Non-Hodgkin’s lymphomas and are B cell in nature. We report a case of primary Diffuse Large B-cell Lymphoma in a 61-year-old male, who presented with a painless swelling in the right parotid region and right sided cervical swelling. The case was initially diagnosed on fine needle aspiration cytology as high grade Non-Hodgkin’s lymphoma and, confirmed and sub-typed on histopathology and immunohistochemistry as primary Diffuse Large B-cell Lymphoma of parotid. The case highlights the role of fine needle aspiration cytology as a timely and accurate diagnostic tool in such a setting, which may help in avoiding unnecessary surgery and complications of surgical interventions.